The roule of anglicisms in modern Ukrainian economic vocabulary. To the question about of the terminology borrowing - Дьолог, Ольга Станіславівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
In this article the problems of borrowing are probed in the modern Ukrainian terminology vocabulary. The role of Anglicism is determined in modern Ukrainian economic terminology. The processes of included in the language of foreign vocabulary and feature of its use are examined. Will be found out the reasons of existence of synonymics pairs of economical terms. Will be noten that modern Ukrainian economical terminology as a part of Ukranian terminology is corresponding with rules of international standarts and world scientific tradition.